Practical introduction to pumping technology a basic guide to pumps, from specifications to installation and operation - Wahren, Uno
Here is a convenient, concise reference book for pump users, application engineers, technicians, and buyers. It contains, in condensed form, valuable information on selecting centrifugal and positive-displacement pumps for given applications, creating the necessary documentation, choosing equipment manufacturers, and checking vendor data. You will find a complete explanation of the types of pumps and the terms and parameters used in pump applications. This book outlines the data required by the client, engineer, and buyer to obtain a comprehensive quote.